Site-specific Investigations of the Earthquake Activities and Hazards for Some Caves in Thailand - Santi Pailoplee (2022)
The seismicity for 35 natural caves in Thailand was investigated probabilistically in order to provide information on their potential earthquake situation. All values representing the earthquake activities within a 300-km radius and the seismic hazard level at each cave were clarified. Seismotectonically, 28 of the 35 caves are situated within previously proposed seismic source zones and most of the seismogenic faults nearby each cave is presently still active, as determined by seismicity and paleoseismological evidence. For the present-day seismicity, the Pla cave in northwest Thailand (situated 0.3km from the Mae Hong Son-Tak fault) showed a comparatively high a-value (4.16) suggesting a high entire seismicity rate, but a relatively high b-value of 0.82. With respect to the b-value, which inversely represents the accumulated seismotectonic stress, the caves at Pha Puang, Lom-Wang, Naresuan and Fha Mue Daeng in the Central-North regions had a comparatively low b-value (<0.5), indicating a high accumulated stress. Based on the recognized earthquake sources and the utilized strong ground-motion attenuation model, the seismic hazard analyses revealed that the caves at Daowadeung, Phra Thart and Lawa in Western Thailand were in the highest seismic hazard areas. This new study contributes to important information for geotourism (e.g. mitigation planning) and selecting/prioritizing speleoseismological investigation sites.